Endoscopic extraction of proximally migrated biliary stent by intrastent balloon inflation. (15th December 2014) - Odemis, Bulent; Beyazit, Yavuz; Tanoglu, Alpaslan; Kayacetin, Ertuğrul
Abstract : Endoscopically placed bile duct stents are commonly used to relieve obstruction in patients with benign or malignant biliary disease. These stents may become dislodged and migrate in about 5–10% of patients. Distally migrated stents can be managed expectantly, allowing the foreign body to pass through the rectum. However, proximal migration of biliary stents usually necessitates endoscopic stent removal. We present a case of a proximally migrated stent that was extracted successfully with intrastent balloon inflation during endoscopic retrograde cholangiopancreatography (ERCP).